2011
DOI: 10.1016/s1130-1473(11)70105-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of complications associated with ultrasound activated resorbable pin osteosynthesis in pediatric craniofacial surgery: preliminary results

Abstract: SummaryUltrasound activated resorbable pin osteosynthesis (UARPO) has recently shown favourable results in operations on children suffering for craniosynostosis. However, data on complications coming with this new technique in children suffering from craniosynostoses are scarce and have only been assessed retrospectively so far. It has been the aim of the present study to prospectively follow up children undergoing craniosynostosis surgery with a focus on complications related to UARPO materials.Ten pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Since the last 5 years, the SonicWeld Rx â System was successfully applied in several clinical case collections (Pilling et al 2007b;Abdel-Galil & Loukota 2008;Aldana et al 2009;Buijs et al 2009;Reichwein et al 2009;Cho et al 2011;Nkenke et al 2011;Schneider et al 2011;V€ olkel et al 2011;Meara et al 2012) in the field of pediatry and craniomaxillofacial surgery. In general, polylactides are successfully applied since 25 years in the craniofacial and orthopedic field.…”
mentioning
confidence: 99%
“…Since the last 5 years, the SonicWeld Rx â System was successfully applied in several clinical case collections (Pilling et al 2007b;Abdel-Galil & Loukota 2008;Aldana et al 2009;Buijs et al 2009;Reichwein et al 2009;Cho et al 2011;Nkenke et al 2011;Schneider et al 2011;V€ olkel et al 2011;Meara et al 2012) in the field of pediatry and craniomaxillofacial surgery. In general, polylactides are successfully applied since 25 years in the craniofacial and orthopedic field.…”
mentioning
confidence: 99%
“…Unfortunately, complications during the resorption process have been described which potentially lead to increased cost of care (10). …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, complications during the resorption process have been described, mainly attributed to the variety and composition of the resorbable polymers (9). Such complications lead to increased cost of care due to added clinic or emergency room visits, imaging, and in some cases, additional surgical procedures (Figure 1) (10). …”
Section: Introductionmentioning
confidence: 99%
“…Some concerns include relative tensile strength compared with metallic plates, particularly its ability to withstand mastication forces, and the extent of inflammation as the material begins to degrade [22]. Meara et al [25] reported using this in conjunction with poly-DL-lactic acid mesh for fixation of Le Fort I osteotomies, whereas others discussed the use in pediatric craniofacial osteosynthesis [19,26]. The SonicWeld Rx (KLS Martin, Jacksonville, FL) is one such system utilizing absorbable plates.…”
Section: Biomaterials and Osteosynthesismentioning
confidence: 99%